The Role of Regulatory and Supervisory Authorities in Enhancing Risk Management in the Construction Sector in the Kingdom of Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to explore the role of regulatory and supervisory bodies in enhancing risk management in the construction sector in the Kingdom of Saudi Arabia. This research comes in light of the major developments witnessed by this sector, which is considered one of the pillars of the national economy, as the need for effective risk management systems is increasing to ensure the sustainability of projects and the achievement of the desired goals. The study used the descriptive analytical approach to reach the desired results, as data was collected through a questionnaire that included 183 individuals working in the construction sector, including engineers, administrators and supervisors in various projects. The study relied on statistical data analysis using the SPSS program to extract results accurately and objectively. The results showed that regulatory and supervisory bodies play a crucial role in enhancing risk management by setting policies and regulations that ensure the reduction of financial, technical and legal risks associated with projects. The results also showed that there is a positive relationship between the effectiveness of regulatory bodies and their ability to manage risks in a way that contributes to improving the quality of projects and increasing their chances of success. Among the most important recommendations reached by the study is the need to enhance cooperation between regulatory bodies and companies operating in the sector to ensure the efficient implementation of policies and procedures, in addition to the importance of training human cadres on modern risk management methods and their practical application in projects. The study also called for the development of advanced technological control systems to improve performance and reduce potential errors.
Keywords: Risk Management; Regulatory Bodies; Regulatory Legislation; Construction Sector; Safety and Quality, Sustainability; Compliance and Standards